EFFECTIVE DOSE COEFFICIENTS FOR RADON AND PROGENY: A REVIEW OF ICRP AND UNSCEAR VALUES - Marsh, James W; Tomášek, Ladislav; Laurier, Dominique; Harrison, John D (Radiation protection dosimetry, 2021)
The International Commission on Radiological Protection (ICRP) publishes guidance on protection against radon exposure in homes and workplaces. ICRP Publication 137 recommends a dose coefficient of 3 mSv per mJ h m-3 (~10 mSv WLM-1) to be used in most circumstances of radon exposure, for workers in buildings and in underground mines. Recently, United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) reviewed radon epidemiology and dosimetry and concluded that its established dose coefficient of 1.6 mSv per mJ h m-3 (5.7 mSv WLM-1) should be retained for use in its comparisons of radiation exposures from different sources in a population. This paper explains and compares the reviews of the scientific evidence from UNSCEAR and ICRP. It is shown that the UNSCEAR and ICRP reviews are consistent and support the use of the ICRP reference dose coefficients for radiation protection purposes. It is concluded that the ICRP dose coefficient should be used to calculate doses to workers.
Keywords: radioaktivní látky znečišťující vzduch; Radon; Radiation Protection; radiační ochrana; Occupational Exposure; lidé; United Nations; Air Pollutants, Radioactive; Radiation Dosage; pracovní expozice; Humans; radon; Organizace spojených národů; dávka záření